Shopping for Change : Consumer Activism and the Possibilities of Purchasing Power - Tohill, Joseph; Hyman, Louis, 1977- (Book collections on Project MUSE., 2017)
"Consuming with a conscience is one of the fastest growing forms of political participation worldwide. Every day we make decisions about how to spend our money and, for the socially conscious, these decisions matter. Political consumers 'buy green' for the environment or they 'buy pink' to combat breast cancer. They boycott Taco Bell to support migrant workers or Burger King to save the rainforest. But can we overcome the limitations of consumer identity, the conservative pull of consumer choice, co-optation by corporate marketers, and other pitfalls of consumer activism in order to marshal the possibilities of consumer power? Can we, quite literally, shop for change? Shopping for Change brings together the historical and contemporary perspectives of academics and activists to show readers what has been possible for consumer activists in the past and what might be possible for today's consumer activists."--Provided by publisher.